Current Solutions for the Treatment of Patients with Urogenital Candidosis and Evaluation of Clinical and Mycologic Efficacy (Texas Journal of Medical Science, 2023)
Objective of the study to determine clinical and mycological efficacy of urogenital candidiasis treatment in dynamics depending on sex and place of residence of patients